Leishmania donovani mediated higher expression of CCL4 induces differential accumulation of CD4+CD56+NKT and CD8+CD56+NKT cells at infection site. (October 2018) - Kumari, Sarita; Shivam, Pushkar; Kumar, Shashank; Jamal, Fauzia; Singh, Manish Kumar; Bimal, Sanjiva; Narayan, Shyam; Pandey, Krishna; Das, Vidya Nand Ravi; Das, Pradeep; Singh, Shubhankar K.
Abstract: Sterile cure from visceralized Leishmania donovani ( L. donovani ) needs Th1 cell support along with the assistance from innate immune cells, NK cells and NKT cells. NKT cells play as a connecting link between innate and adaptive immune cell and support T helper cell function. Earlier, a categorical function of CD56 positive CD4 + or CD8 + NKT cells was reported in visceral leishmaniasis (VL). It was observed in in vitro that CD4 + CD56 + NKT cells, but not CD8 + CD56 + NKT cells, were accumulated at the L. donovani infection site. Therefore, in vitro experiments have been carried out to decipher the mechanism behind preferential accumulation of CD4 + CD56 + NKT cells at infection site. In this study, 1.89 fold higher expression of CCL4/MIP-1β was noticed in infected macrophages. The higher expression of CCL4 was correlated with preferential accumulation of CCR5 + CD4 + CD56 + NKT cells and apoptosis of CD8 + CD56 + NKT cells at in vitro infection site. The CD4 + CD56 + NKT cells were also observed expressing TGF-β dominantly. Interaction of CCL4 chemotaxis was interrupted by blocking, which led to drift back the TGF-β producing CD4 + CD56 + NKT cells and promoted CD8 + CD56 + NKT cells recruitment in in vitro infection site. CCR5 blockade also reduced CD25 and FoxP3 positive CD4 + CD56 + NKT cells in in vitro infection site. Therefore, it was concluded that Leishmania promotes strategic expression of CCL4, which alternately attracts CCR5 + cells, mostly expressing regulatory cytokines, at infection site. This reduces the CD8 + CD56 + NKT cells at infection site through Smad4 mediated TGF-β expression and activation of caspases. Data indicates that L. donovani induces higher expression of CCL4 in host cell to attract CCR5 + cells under its strategic plan to downregulate host immune response.